Chương I - Căn bậc hai. Căn bậc ba

Nghiêu Nghiêu

cho biểu thức

\(M=\dfrac{3-\sqrt{3+\sqrt{3+\sqrt{3+...+\sqrt{ }}}}}{6-\sqrt{3+\sqrt{3+\sqrt{3+..\sqrt{3}}}}}\)

tử số co 2014 dấu căn, mẫu số có 2013 dấu căn. chứng minh: M<\(\dfrac{1}{4}\)

Nguyễn Quỳnh
26 tháng 11 2017 lúc 15:09

Ta có :Đặt t = \(\sqrt{3+\sqrt{3+\sqrt{3+...+\sqrt{3}}}} ( 2014 dấu căn )\)

\(\Rightarrow\) t > \(\sqrt{3} > \sqrt{1} = 1\)

\(\Rightarrow\) \(\sqrt{3+\sqrt{3+\sqrt{3+...+\sqrt{3}}}}\)(2013 dấu căn ) = \(t^2 -3\)

Do đó : \(M = \frac{3-t}{6-( t^2 - 3 )}\)= \(\frac{3-t}{9-t^2}\) = \(\frac{3-t}{(3-t)(3+t)}\) = \(\frac{1}{3+t}\)

Vì t>1 \(\Rightarrow\) 3+t > 4 \(\Rightarrow\) \(\frac{1}{3+t}\) < \(\frac{1}{4}\)

Vậy M < \(\frac{1}{4}\)

Bình luận (0)

Các câu hỏi tương tự
Phú Phạm Minh
Xem chi tiết
duy Nguyễn
Xem chi tiết
Nozomi Judo
Xem chi tiết
Phạm Ngọc Minh
Xem chi tiết
Huyền Trang
Xem chi tiết
Lê Hương Giang
Xem chi tiết
Emily Nain
Xem chi tiết
Ly Ly
Xem chi tiết
Biện Bạch Ngọc
Xem chi tiết